Real-Time Release Testing (RTRT) in Pharmaceutical Quality Control: Current Practices and Future Prospects - Dandekar, Mayur Rajeshwar; Mirzapure, Isha anil; Salve, Yash Manoj; Khobragade, Deepak (International Journal of Pharmaceutical Investigation, 2026)
Real-time release Testing is now considered one of the breakthroughs in pharmaceutical quality control, replacing the old batch-testing paradigms with a modern, real-time, more efficient, data-driven approach. RTRT combines real-time application of process control, process data, and analytical data as well as innovative controlling systems that check the quality of a product in the production phase and comply with the requirements of the two regulators while at the same time reducing the time taken in the production process. This article aims to review current practices, regulations, and methods used in RTRT, especially in fast-growing and developing pharmaceutical production processes. We then review several issues surrounding it, including the necessity of high-form technologies, cost, and regulatory concerns. Moreover, the paper also discusses the future of RTRT, such as the integration of the technique in industries under Industry 4.0, the application of RTRT in the field of personalized medicine, and the globalization of regulatory policies. As more pharmaceutical manufacturers begin to adopt such innovative practices as part of their continuous improvement strategies, RTRT is well-positioned to significantly boost product quality, manufacturing efficiency, and patient safety, marking the beginning of a new era of pharmaceutical quality assurance.
Keywords: Real-Time Release Testing (RTRT); Pharmaceutical Quality Control; Process Analytical Technology (PAT); Regulatory Framework; Continuous Manufacturing; Data Analytics; Industry 4.0; Personalized Medicine.